Exploring Teachers’ Expectation in Students’ English Learning Motivation - Melsin Martinus; B, Lumoindong (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study investigates the influence of teachers’ expectations lead to improved performance on students’ motivation in learning English. Focusing on English major students at Universitas Klabat, the research employs a qualitative design utilizing thematic analysis of semi-structured interviews with four participants. The main question addressed in this study is: What are the students’ perspectives of teachers’ expectations on students’ motivation in learning English in terms of (a) Nature of Teacher Expectations, (b) Communication of Expectations, (c) Impact on Motivation, (d) Support Needed, and (e) Effect of Low Expectations? The study uses a qualitative approach, collecting data through semi-structured interviews with four students. Results show that when teachers set clear and realistic expectations, students tend to be more motivated, putting in extra effort and participating more actively in class. On the other hand, unclear or overly high expectations can lead to stress or a drop in motivation. Interestingly, one student remained driven by personal goals, regardless of teacher expectations, highlighting that not all students respond the same way. Overall, the study suggests that teacher expectations can be a powerful motivator when used effectively and supported with proper feedback and encouragement.